AN EMPIRICAL STUDY OF THE FACTORS RESPONSIBLE FOR THE HIGH PREVALENCE OF VIDEO FILM PIRACY IN NIGERIA - Ridwan, Adeyemi A.; Akashoro, Ganiyu; Ajaga, Mukaila (European Scientific Journal, ESJ, 2013)
﻿Recent studies have shown that the trend of video piracy in Nigeria has been very high and quite worrisome. Most of the studies however were conducted by foreign scholars and organizations, thus findings of such studies have been criticized to be biased, politicized and inexhaustive. The NCC (2008) study has been the only known study yet on copyright piracy from an insider’s perspective. However, the study has also been criticized as being too broad as it surveyed the piracy of many copyrighted products and not specifically focused on video piracy and hence not quite exhaustive on video piracy. Besides, the NCC study was conducted by a government video regulatory agency and sponsored by another foreign donor agency, the Ford foundation, UK, hence the need for an independent scholarly, Nigerian-oriented or “Nigerian perspective” study to empirically investigate the factors responsible for the high prevalence of video piracy in Nigeria. Logically therefore, the objective of this study was to investigate the factors responsible for the high prevalence of video piracy in the Nigerian society. The qualitative research design was adopted for the study which includes; the use of case study approach focused on Lagos, the Nigerian largest mega-city; the triangulation of in-depth interview, focus group discussion as well as document analysis of the data collection. A triangulation of the interpretive and critical analytical methods was also adopted for the data analysis. The findings of this study reveal twelve different factors as being responsible for the high prevalence of video piracy in the Nigerian society. The significance of this study lies in its update of knowledge on video piracy discourse and videography; its provision of empirical evidence for the government to mirror itself and understand its lapses in relation to the video piracy problem and the entire Nigerian video industry; provision of valuable evidence which engenders the government to take appropriate redemption steps towards eradicating video piracy; serves the benefit of teaching and increasing the security consciousness of Nigerian business entrepreneurs and video investors; and finally, this study further engenders the need for increased awareness campaign among the public and the need for a change of strategies on video production and marketing as well as on awareness campaigns on video piracy, thus paving way for better results in anti-piracy drives.